Analysis Of Factors Influencing The Incident Of Ari In Toddler In The Lararan Rejosari Village Of Wonosobo - Susanto, Setyo Budi; Nimas Sitoresmi (Journal for Quality in Public Health, 2024)
Acute respiratory infections (ARI) are one of the highest causes of death in people in developing countries. The aim of this research was to analyze the effect of air ventilation, residential density and room lighting on the incidence of ARI in toddlers in Larangan Hamlet, Rejosari Village, Wonosobo. The design of this research is quantitative observational research with a cross sectional approach with the focus of the research directed at analyzing the influence of air ventilation, residential density and room lighting on the incidence of ARI in toddlers in Larangan Hamlet, Rejosari Village, Wonosobo. The total population was 53 respondents and the sample was 47 respondents taken using the Simple Random Sampling technique. The findings showed that the majority of respondents had ventilation in the qualifying category, namely 29 respondents (69.05%). Most of the respondents had a residential density category that met the requirements, 31 respondents (72.81%). Most respondents had room lighting in the category that did not meet the requirements, as many as 27 respondents (64.29%). The majority of respondents did not experience ARI, 34 respondents (80.95%). Based on the results of the Logistic Regression analysis, it shows that the p-value is <0.05, so H1 is accepted, so it is concluded that there is an influence of air ventilation, residential density and room lighting on the incidence of ISPA in toddlers in Larangan Hamlet, Rejosari Village, Wonosobo. Overall, good ventilation, low residential density, and adequate room lighting are important factors in reducing the risk of ARI in toddlers. Implementing steps to improve this condition in homes in Larangan Hamlet, Rejosari Village, Wonosobo can help reduce the incidence of ARI and improve the respiratory health of toddlers.